Ultrasound Assessment of the Change in Carotid Corrected Flow Time in Fluid Responsiveness in Undifferentiated Shock. Issue 11 (November 2018) - Barjaktarevic, Igor; Toppen, William E.; Hu, Scott; Aquije Montoya, Elizabeth; Ong, Stephanie; Buhr, Russell; David, Ian J.; Wang, Tisha; Rezayat, Talayeh; Chang, Steven Y.; Elashoff, David; Markovic, Daniela; et al.
Abstract : Objectives: Adequate assessment of fluid responsiveness in shock necessitates correct interpretation of hemodynamic changes induced by preload challenge. This study evaluates the accuracy of point-of-care Doppler ultrasound assessment of the change in carotid corrected flow time induced by a passive leg raise maneuver as a predictor of fluid responsiveness. Noninvasive cardiac output monitoring (NICOM, Cheetah Medical, Newton Center, MA) system based on a bioreactance method was used. Design: Prospective, noninterventional study. Setting: ICU at a large academic center. Patients: Patients with new, undifferentiated shock, and vasopressor requirements despite fluid resuscitation were included. Patients with significant cardiac disease and conditions that precluded adequate passive leg raising were excluded. Interventions: Carotid corrected flow time was measured via ultrasound before and after a passive leg raise maneuver. Predicted fluid responsiveness was defined as greater than 10% increase in stroke volume on noninvasive cardiac output monitoring following passive leg raise. Images and measurements were reanalyzed by a second, blinded physician. The accuracy of change in carotid corrected flow time to predict fluid responsiveness was evaluated using receiver operating characteristic analysis. Measurements and Main Results: Seventy-seven subjects were enrolled with 54 (70.1%) classified as fluid responders by noninvasive cardiac output monitoring. The average change in carotid corrected flow time after passive leg raise for fluid responders was 14.1 ± 18.7 ms versus –4.0 ± 8 ms for nonresponders ( p < 0.001). Receiver operating characteristic analysis demonstrated that change in carotid corrected flow time is an accurate predictor of fluid responsiveness status (area under the curve, 0.88; 95% CI, 0.80–0.96) and a 7 ms increase in carotid corrected flow time post passive leg raise was shown to have a 97% positive predictive value and 82% accuracy in detecting fluid responsiveness using noninvasive cardiac output monitoring as a reference standard. Mechanical ventilation, respiratory rate, and high positive end-expiratory pressure had no significant impact on test performance. Post hoc blinded evaluation of bedside acquired measurements demonstrated agreement between evaluators. Conclusions: Change in carotid corrected flow time can predict fluid responsiveness status after a passive leg raise maneuver. Using point-of-care ultrasound to assess change in carotid corrected flow time is an acceptable and reproducible method for noninvasive identification of fluid responsiveness in critically ill patients with undifferentiated shock. Abstract : Supplemental Digital Content is available in the text.